Enhancing deep-UV emission at 234 nm by introducing a truncated pyramid AlN/GaN nanostructure with fine-tuned multiple facets. Issue 3 (12th January 2022) - Lu, Shiqiang; Jiang, Xinjun; Wang, Yaozeng; Huang, Kai; Gao, Na; Cai, Duanjun; Zhou, Yinghui; Yang, C. C.; Kang, Junyong; Zhang, Rong
Abstract : A unique truncated pyramid nanostructure with fine-tuned multiple facets is fabricated into a (AlN)8 /(GaN)2 digital alloy. As reflecting mirrors, the multiple facets can effectively modulate the light extraction patterns and lead to highly efficient 234 nm DUV emission. Abstract : The external quantum efficiency of a high-Al content (>0.6) AlGaN deep-ultraviolet (DUV) light-emitting diode is typically below 1% in the sub-250 nm wavelength range. One of the main reasons for this low efficiency is the fundamental properties of high-Al content AlGaN comprising the transverse-magnetic (TM)-dominant emission and low light extraction due to the total internal reflection (TIR). This work demonstrates a truncated pyramid nanostructure with fine-tuned multiple facets in an (AlN)8 /(GaN)2 digital alloy to achieve highly efficient DUV emission at 234 nm. By applying nanoimprint lithography, dry and wet etching, a hexagonal truncated pyramid nanohole structure is fabricated featuring multiple crystal facets of (0001), (10-13), and (20-21) planes. These fine-tuned multiple facets act as reflecting mirrors that can effectively modulate the light propagation and extraction patterns to overcome the TIR via multiple reflections and enhanced scattering. Consequently, significant light extraction enhancements of 5.6 times and 1.1 times for TM and transverse-electric emissions are achieved in the truncated pyramid nanohole structure, respectively. The total luminous intensity of this unique nanostructure is greatly increased by 191% compared to that of a conventional planar structure. The truncated pyramid AlN/GaN nanostructure with fine-tuned multiple facets used in this work provides a promising approach for realizing highly efficient sub-250 nm DUV light-emitting devices.